Dilemmas of consumption habits - comparison of the quality of bottled mineral water and the public utility drinking water in Debrecen - Nagy, Sándor (Acta Agraria Debreceniensis, 2012)
This paper tries to help to decide whether the bottled mineral water or the piped water is more advisable for consumption in Debrecen and in its regions, according to the aspects of environmental awareness and aspects of health, beside the venture of representing the functions of water in our lives and its global importance.